Interrelationship between decentralization of energy sources and their renewability: A bibliometric analysis of research trends and thematic evolution - Anargul Belgibayeva; Artem Artyukhov; Viera Kubičková; Miroslava Čukanová; Iuliia Myroshnychenko; Ihor Ruzhytsky; Serhiy Lyeonov (Environmental Economics)
Type of the article: Research Article AbstractDecentralization and renewable energy have gained significant global attention due to their potential to enhance energy security, promote sustainability, and democratize energy access. This study aims to provide a comprehensive bibliometric analysis of research trends, key contributors, and thematic developments in the field of the decentralization of energy sources and their renewability. The research methodology involves a bibliometric analysis based on data extracted from the Scopus database, covering publications from 1973 to 2025. The analysis reveals exponential growth in research output, particularly after 2014, with over 3,700 publications recorded in 2023 alone. Citation trends indicate that foundational studies on decentralized microgrids and distributed energy systems remain highly influential, while recent works on blockchain-based energy trading and AI-driven energy management are gaining prominence. The study identifies China (11.7% of total publications), the United States (6.5%), and India (5.7%) as the leading contributors, with significant research activity also observed in European countries. Additionally, journals such as Applied Energy, Renewable Energy, and Energies serve as the primary publication platforms in this domain. Thematic analysis highlights a shift from bioenergy and land-use studies toward smart grids, energy storage, artificial intelligence, and decentralized finance for energy markets. Furthermore, co-authorship and international collaboration have increased significantly, with 25% of papers involving multi-country research efforts. Keyword analysis indicates growing research interest in emerging topics such as hydrogen energy, demand-side management, and digitalization in decentralized energy systems. These findings underscore the increasing interdisciplinary nature of decentralized energy research, integrating technological, economic, and policy dimensions. AcknowledgmentThis study was prepared as part of the project IZURZ1_224119/1 (Swiss National Science Foundation).